Studi Exploratory atas Faktor Penentu Konsumen Berkunjung di Mall Tatura Palu Sulawesi Tengah - Asngadi Asngadi (Jurnal Aplikasi Manajemen, 2012)
Business competition in this time, has made management of shopping center must know and fulfill consumers expectation quickly. The concept of shopping centre development as one places to fulfill all requirement, has made shopping centre not only become place to go to shopping, but also has become center of family recreation, center of business information, center of technological development information. Consumer behaviour in choosing shopping centre imply not only determined by availability of goods on the super market, but also considered other factors. Based on these reasons, it is important to study factors determine customers visit to shopping centre especially in Tatura Mall, Palu Central Sulawesi. The aim of this is: To know and analyze factors considered by community in Palu to visit in Tatura Mall 2) To determine a dominant factor influencing consumer to visit in Tatura Mall. This research implemented exploratory study by using Principle Component Analysis (PCA) method. Result of this research shows that, there are 5 (five) dimensions why customer visit in Tatura Mall, that are: 1) Fulfill leasure time, consisted of items: to look for new experience in shopping; accompanies child to play a game; fulfill leasure time with family; refreshing and tries new product on the market.2) Comfortable in shopping, consisted of items: low prices; wide parking areas; and shopping. 3) Presstiges, consisted of items: prestigious places, new life style 4) Location: near by home, easy to access 5)Technology: to try several new technology in Tatura Mall, computer fair, sport center, vehicle shows. Of all the factors above, Fulfill leasure time is a dominant factor than others, with Eigenvalue 2,861 and variance explained 15,896.Keywords: exploratory study, leasure time, comfortable , presstigeous, Location, technology.